Komuniciranje podnebne krize v književnosti: primer pisateljice Nataše Kramberger - Čeh Steger, Jožica (Komuniciranje okoljske krize, 2025)
The present contribution draws from the premise that the global perception of the climate crisis is a socio-cultural problem and thus an integral part of public discourse, where literature can also play a significant role. Compared to professional (technical) explanations, climate fiction has the ability to concretize the abstractness of climate change with tangible narratives and real-life experiences of present-day individuals. Following the descriptions of the characteristics and specifics of climate fiction in the framework of ecocriticism, in the framework of which the climate change novel after the year 2000 occupies a prominent position, this paper focuses on the literary activities and environmental activism of the writer and ecological farmer Nataša Kramberger. Based on the viewpoint of climate change thematization, the autobiographically designed ecological novel Primerljivi hektarji [Comparable Hectares] (2017) and the genre hybrid Po vsej sili živ [Struggling to Survive] (2024) will be presented. Here, Nataša Kramberger speaks of the difficulties and significance of organic farming in times of the ever-worsening climate situation.